Platelets are indispensable for alveolar development in neonatal mice - Huang, Zilu; Lin, Bingchun; Han, Dongshan; Wang, Xuan; Zhong, Junyan; Wagenaar, Gerry T. M.; Yang, Chuanzhong; Chen, Xueyu (Frontiers in Pediatrics, 2022)
Previous studies suggest that platelets are involved in fetal and adult lung development, but their role in postnatal lung development especially after premature birth is elusive. There is an urgent need to scrutinize this topic because the incidence of bronchopulmonary dysplasia (BPD), a chronic lung disease after premature birth, remains high. We have previously shown impaired platelet biogenesis in infants and rats with BPD. In this study we investigated the role of anti-CD41 antibody-induced platelet depletion during normal postnatal lung development and thrombopoietin (TPO)-induced platelet biogenesis in mice with experimental BPD. We demonstrate that platelet deficient mice develop BPD-like phenotype, characterized by enlarged alveoli and vascular remodeling of the small pulmonary arteries, resulting in pulmonary arterial hypertension (PAH)-induced right ventricular hypertrophy (RVH). Vascular remodeling was potentially caused by endothelial dysfunction demonstrated by elevated von Willebrand factor (vWF) concentration in plasma and reduced vWF staining in lung tissue with platelet depletion. Furthermore, TPO-induced platelet biogenesis in mice with experimental BPD improved alveolar simplification and ameliorated vascular remodeling. These findings demonstrate that platelets are indispensable for normal postnatal lung development and attenuation of BPD, probably by maintaining endothelial function.